2015
DOI: 10.1038/cmi.2015.89
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of the Treg/Th17 balance by mesenchymal stem cells in human systemic lupus erythematosus

Abstract: UC MSCs up-regulate Treg and down-regulate Th17 cells through the regulation of TGF-β and PGE2 in lupus patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
141
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 188 publications
(159 citation statements)
references
References 33 publications
10
141
0
2
Order By: Relevance
“…The main T cell subsets which are pivotal for this T cell balance consist of T helper (Th) cells and regulatory T (Treg) cells, and moreover, Th cells are defined as Th1, Th2 and Th17 subtypes characterized by differential expression of certain cytokines. In SLE, increasing evidences have demonstrated that the disrupted balance between Th cells and Treg cells contributed to the disease development [59]. Deficiencies of Treg cells, either quantitative or functional, were found in active lupus patients, while the number of Th17 cells, as well as Th17-related cytokines, was found increased in SLE patients [1012].…”
Section: Adenosinergic Pathway Regulates Immune Imbalance During Automentioning
confidence: 99%
“…The main T cell subsets which are pivotal for this T cell balance consist of T helper (Th) cells and regulatory T (Treg) cells, and moreover, Th cells are defined as Th1, Th2 and Th17 subtypes characterized by differential expression of certain cytokines. In SLE, increasing evidences have demonstrated that the disrupted balance between Th cells and Treg cells contributed to the disease development [59]. Deficiencies of Treg cells, either quantitative or functional, were found in active lupus patients, while the number of Th17 cells, as well as Th17-related cytokines, was found increased in SLE patients [1012].…”
Section: Adenosinergic Pathway Regulates Immune Imbalance During Automentioning
confidence: 99%
“…Allogeneic MSCT in lupus mice and humans could change the immune cell imbalance in vivo, including T helper 17 cells, regulatory T cells, plasma cells [10][11][12]. Recently, Liu et al [13] showed that allogeneic MSCT could rescue autologous bone marrow MSCs function and ameliorate osteopenia in Fas-deficient-MRL/lpr mice, which could change the epigenetic cascade in vivo.…”
Section: Introductionmentioning
confidence: 96%
“…The generation of CD4 + CD25 + Foxp3 + Tregs is reciprocally linked with IL-17 + CD4 + Th17 and IFN-γ + CD4 + Th1 cells [47,48]. Because IDO may regulate the equilibrium of CD4 + Foxp3 + Tregs and IL-17 + CD4 + Th17 cells in inflammatory diseases [49,50], we examined the generation of each CD4 + Th subset, including CD4 + Foxp3 + Tregs, IL-17 + CD4 + Th17, and IFN-γ + CD4 + Th1 cells, early during JE progression. Our results revealed that IDO-ablated mice showed no significant alterations in the frequency or number of CD4 + CD25 + Foxp3 + Tregs, compared to wild-type BL/6 mice ( Fig.…”
Section: Ido Ablation Induces a Skewed Ifn-γ + Cd4 + Th1 Response Durmentioning
confidence: 99%